2017
DOI: 10.1590/0102-311x00118816
|View full text |Cite
|
Sign up to set email alerts
|

Atenção primária integral e sistemas segmentados de saúde na América do Sul

Abstract: Resumo O artigo analisa o processo recente de reformas da atenção primária à saúde nos países da América do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
27

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 15 publications
0
19
0
27
Order By: Relevance
“…In addition, there were some disagreements among the interviewees with the reading of summaries. Other studies in different regions of Brazil revealed the same characteristics as the Regional Interagency Committee which we analysed [3334], however, this forum acts as an important indicator of the effectiveness of regionalization [3536]. …”
Section: Discussionmentioning
confidence: 80%
“…In addition, there were some disagreements among the interviewees with the reading of summaries. Other studies in different regions of Brazil revealed the same characteristics as the Regional Interagency Committee which we analysed [3334], however, this forum acts as an important indicator of the effectiveness of regionalization [3536]. …”
Section: Discussionmentioning
confidence: 80%
“…Ademais, a inexistência de PCCS apontada pela maioria dos profissionais se refere à frágil interferência estatal na construção de um plano de carreira para a ESF 6 , bem como à incipiência na instituição desse instrumento, de forma geral no Brasil, com mais dificuldades de implantação desses em municípios de menor porte 7 .…”
Section: ▄ Discussãounclassified
“…Estudos apontam que a predominância desses vínculos precários, com perdas de direitos trabalhistas, é crescente no setor público e, por consequência, na ESF, resultando em instabilidade e insegurança aos profissionais, sendo apontados como principais responsáveis pela alta rotatividade deles 6,27 . Para Giovanella e Almeida 6 , a precariedade dos vínculos indica fraca intervenção estatal no direcionamento da força de trabalho para o sistema público de saúde. Embora não seja uma realidade no norte de Minas, Garrido-Pinzón e Bernardo 28 discorrem sobre os novos arranjos na gestão do trabalho, com a inserção da terceirização, entre outras formas de contratação, que resultam em vulnerabilização social do trabalhador da saúde.…”
Section: ▄ Discussãounclassified
See 1 more Smart Citation
“…In this perspective, strategies for developing health anchored in the structures of the social formations, supported by health professionals, were elaborated in local health units, responsible for the greater part of care. [1][2][3] This represented an attempt to overcome the predominant health care model, marked by the paradigm of disease and fragmentation, to the detriment of integrality.…”
Section: Introductionmentioning
confidence: 99%